Molecular Pathology of Lung Diseases - Zander, Dani S.; Popper, Helmut; Jagirdar, Jaishree; Haque, Abida; Barrios, Roberto; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2008)
Molecular Pathology of Lung Diseases, the first volume in the Molecular Pathology Library Series under the series editorship of Philip T. Cagle, MD provides a bridge between clinical pulmonary pathology and basic molecular science. It is designed to provide a practical disease-based overview that will be useful to pathologists, pulmonologists, thoracic surgeons and other health care providers interested in lung disease. The first two sections of the volume provide the reader with general concepts, terminology and procedures in molecular pathology. The remainder of the volume is subdivided into neoplastic and non-neoplastic lung diseases with detailed chapters covering the current molecular pathology of specific diseases.
Basic Concepts of Molecular Pathology -- Genes, Gene Products, and Transcription Factors -- Receptors, Signaling Pathways, Cell Cycle, and DNA Damage Repair -- Cell Adhesion Molecules -- Apoptosis and Cell Death: Relevance to Lung -- Roles of Mutation and Epimutation in the Development of Lung Disease -- Techniques and Experimental Systems in Molecular Pathology -- Bioinformatics and Omics -- General Approach to Molecular Pathology -- Applications of Molecular Tests in Anatomic Pathology -- Polymerase Chain Reaction and Reverse Transcription&##x2014;Polymerase Chain Reaction -- Array Comparative Genomic Hybridization in Pathology -- Loss of Heterozygosity in Lung Diseases -- In Situ Hybridization: Principles and Applications for Pulmonary Medicine -- Proteomics -- Animal Models of Lung Disease -- Tissue Culture Models -- Molecular Pathology of Pulmonary and Pleural Neoplasms: General Principles -- Molecular Oncogenesis of Lung Cancer -- Genetic Susceptibility -- Prognostic Markers -- Pulmonary Angiogenesis in Neoplastic and Nonneoplastic Disorders -- Lung Cancer Stem Cells -- Gene Therapy Approaches for Lung Cancer -- Response to Conventional Therapy and Targeted Molecular Therapy -- Environmental Agents in Lung and Pleural Neoplasms -- Viral Oncogenesis -- Molecular Pathology of Pulmonary and Pleural Neoplasms: Specific Histologic Types -- Adenocarcinoma and Its Precursor Lesions -- Molecular Pathology of Squamous Cell Carcinoma and Its Precursors -- Molecular Pathology of Large Cell Carcinoma and Its Precursors -- Small Cell Carcinoma -- Neuroendocrine Carcinomas and Precursors -- Pulmonary Lymphomas -- Posttransplantation Lymphoproliferative Disorder -- Unusual Benign and Malignant Neoplasms of Lung: Molecular Pathology -- Primary Versus Metastatic Cancer: Gene Expression Profiling -- Diffuse Malignant Mesothelioma: Genetic Pathways and Mechanisms of Oncogenesis of Asbestos and Other Agents That Cause Mesotheliomas -- Molecular Pathology of Pediatric Tumors of the Lung -- Molecular Pathology of Pulmonary Infections -- Basis of Susceptibility to Lung Infection -- Molecular Pathology of Viral Respiratory Diseases -- Molecular Pathology of Rickettsial Lung Infections -- Bacteria -- Immunopathology of Tuberculosis -- Molecular Pathology of Fungal Lung Infection -- Parasites -- Molecular Pathology of Other Nonneoplastic Pulmonary Diseases: General Principles -- Inflammation -- Oxidants and Antioxidants -- Epithelial Repair and Regeneration -- Fibrogenesis -- Stem Cells in Nonneoplastic Lung Disorders -- Gene Therapy in Nonneoplastic Lung Disease -- Molecular Pathology of Other Nonneoplastic Pulmonary Diseases: Specific Entities -- Smoking-Related Lung Diseases -- Heritable ?1-Antitrypsin Deficiency -- Asthma -- Cystic Fibrosis -- Pulmonary Organogenesis and Developmental Abnormalities -- Genetic Abnormalities of Surfactant Metabolism -- Usual Interstitial Pneumonia -- Sarcoidosis: Are There Sarcoidosis Genes? -- Histiocytic Diseases of the Lung -- Pulmonary Arterial Hypertension -- Immunopathology of Pulmonary Vasculitides -- Asbestosis and Silicosis.
Keywords: Pathology; Respiratory organs—Diseases.; Pathology; Pneumology/Respiratory System